Preparation of immunoliposomes by direct coupling of antibodies based on a thioether bond - Petrilli, Raquel; Eloy, Josimar O. [UNESP]; Lee, Robert J.; Lopez, Renata F. V. (Springer Nature, 2018)
Drug delivery is of paramount importance, since the drug needs to be delivered to a specific site, in adequate concentration, avoiding degradation in order to provide therapeutic efficacy. Different nanocarriers have been used over the years for this purpose and liposomes are well-established systems due to the high biocompatibility and the possibility to vehiculate both hydrophilic and lipophilic drugs. In order to circumvent the rapid clearance by the reticuloendothelial system and to avoid the healthy cells exposure to the drug, long circulating liposomes containing polyethyleneglycol (PEG) and functionalized liposomes for targeted delivery have been developed. Immunoliposomes consist of liposomes containing antibodies or antibody fragments attached at the membrane surface. This attachment can be performed using PEG lipids, containing a reactive terminal group such as maleimide and thiolated antibodies. Additionaly, the use of PEG chains as spacers increases antibody–antigen affinity, since the antibody is not shielded by the steric hindrance of PEG and also due to the correct orientation of antibodies for interaction with receptors on cell surface. In this chapter, we describe and discuss in details the protocol to prepare anti-epidermal growth factor receptor (anti-EGFR) and anti-human epidermal growth factor receptor 2 (anti-HER2) liposomes using cetuximab and trastuzumab as antibodies. We present the direct coupling method based on the maleimide thioether reaction for these immunoliposomes preparation and present some characterization steps and in vitro studies in cell culture which can be used for better understanding these nanocarriers.
Keywords: Cetuximab; Covalent coupling; Direct conjugation; Immunoliposomes; Targeting; Trastuzumab